The Relationship Between Collective Self-Esteem, Acculturation, and Alcohol-Related Consequences Among Asian American Young Adults - PEDERSEN, ERIC R. (J Ethn Subst Abuse, 2013)
We examined the relationship between collective self-esteem (i.e., the value one places on being part of a collective group), acculturation, and alcohol-related consequences in a sample of 442 Asian American young adults. We found that membership self-esteem and public collective self-esteem interacted with acculturation such that low levels of both predicted greater rates of consequences. Participants with lower acculturation and greater private collective self-esteem experienced more alcohol consequences. This study suggests that differential aspects of collective self-esteem may serve as protective or risk factors for Asian American young adults depending on degree of acculturation.